Videogames and virtual assets exchange - Garrido, Flavio A. (2021)
With the increase of the online videogame industry and the acceptance of the players to invest time and real money in the games, the developers create new business models for selling virtual assets. This works is part of a postgraduate thesis in development and examines the business of video games, virtual assets, why players spend real money and the advantage of a common market between different games would have to increase the profits of the developers and allow the time invested by the players to also give them profits.